Network topology of stable isotope interactions in a sub-arctic raptor guild - Dalerum, F.; Hellström, P.; Miranda, M.; Nyström, J.; Ekenstedt, J.; Angerbjörn, A. (Oecologia, 2016)
Predation is an ecologically important process, and intra-guild interactions may substantially influence the ecological effects of predator species. Despite a rapid expansion in the use of mathematical graph theory to describe trophic relations, network approaches have rarely been used to study interactions within predator assemblages. Assemblages of diurnal raptors are subject to substantial intra- and interspecific competition. Here we used the novel approach of applying analyzes based on network topology to species-specific data on the stable isotopes ¹³C and ¹⁵N in feathers to evaluate patterns of relative resource utilization within a guild of diurnal raptors in northern Sweden. Our guild consisted of the golden eagle (Aquila chrysaetos), the gyrfalcon (Falco rusticolus), the peregrine falcon (Falco peregrinus) and the rough-legged buzzard (Buteo lagopus). We found a modular trophic interaction structure within the guild, but the interactions were less nested than expected by chance. These results suggest low redundancy and hence a strong ecological importance of individual species. Our data also suggested that species were less connected through intra-guild interactions than expected by chance. We interpret our results as a convergence on specific isotope niches, and that body size and different hunting behaviour may mediate competition within these niches. We finally highlight that generalist predators could be ecologically important by linking specialist predator species with disparate dietary niches.